2022
DOI: 10.3389/fsurg.2022.961258
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of appendicitis management during COVID-19 pandemic: A study of Chinese adult cohorts

Abstract: BackgroundHealthcare seeking behavior has been widely impacted due to the restricted movements of individuals during the Coronavirus disease-19 (COVID-19) pandemic. This study aims to perform risk stratification in patients requiring timely intervention during the recovery periods.MethodsOperation notes of acute appendicitis (AA) patients within a hospital were analyzed during three six-month periods (23 January-23 July in 2019, 2020, and 2021, respectively). Patient data were collected retrospectively includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
2
1
Order By: Relevance
“…The introduction of mandatory PCR testing for medical treatment seekers, except in emergency cases, has notably influenced the management of appendicitis, a common cause of abdominal pain and a leading indicator for emergency abdominal surgery worldwide [ 16 ]. While studies in some regions reported increased time from symptom onset to hospital visit and more complex cases due to these measures [ 7 , 17 ], our study, in alignment with other Chinese retrospective cohorts, found no significant differences in the management of appendicitis in China [ 10 ]. These findings suggest minimal influence on appendicitis patients’ seeking behaviors in China, potentially attributed to cultural nuances.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The introduction of mandatory PCR testing for medical treatment seekers, except in emergency cases, has notably influenced the management of appendicitis, a common cause of abdominal pain and a leading indicator for emergency abdominal surgery worldwide [ 16 ]. While studies in some regions reported increased time from symptom onset to hospital visit and more complex cases due to these measures [ 7 , 17 ], our study, in alignment with other Chinese retrospective cohorts, found no significant differences in the management of appendicitis in China [ 10 ]. These findings suggest minimal influence on appendicitis patients’ seeking behaviors in China, potentially attributed to cultural nuances.…”
Section: Discussionsupporting
confidence: 70%
“…A critical finding of our study is the prolonged interval from emergency room admission to surgery during the pandemic, primarily due to the implementation of additional procedures such as real-time PCR testing [ 18 ], which takes approximately 4–6 h [ 10 ]. Although delayed surgical intervention can potentially exacerbate inflammation and complications, our study observed no direct impact on complication rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients undergoing operative management for appendicitis during the pandemic were assessed to have poorer overall health, as determined by their significantly higher ASA scores. This was not identified in other studies, which all reported no significant difference between the pandemic and control cohort ASA scores [ 37 , 38 , 42 ]. There are a number of explanations why our findings differed from other studies; the studies were conducted in different countries with differing health care systems, and the ASA is a subjective measure.…”
Section: Discussioncontrasting
confidence: 55%